Design and Implementation of 4WD Intelligent Car System Based on Integrated Navigation - Jie Tao; Xin Wang; Jiazhen Si (Innovation in Science and Technology, 2023)
Focuses on the basic principle of integrated navigation system based on geomagnetic sensor, three-axis gyroscope and three-axis accelerometer. A four-wheel independent driving car platform is designed with STM32F4 MCU as the control core and RZ7899 as the motor drive. The vehicle heading angle is obtained through the quaternion obtained by MPU6050, and combined with the geomagnetic parameters, the serial double PID control algorithm is used for navigation by correcting the deflection angle, the intelligent car can run in a straight line without other navigation systems within a certain range.